ABNORMAL FREE GAS COLLECTION IN RADIOGRAPHY: A PICTORIAL REVIEW - Tjakraatmadja, Ricardo; Erawati, Dini Rachma (Department of Radiology, Medical Faculty, University of Brawijaya, 2022)
An abnormal free gas collection in the thorax and abdomen is a condition which is present of abnormal air in the thorax and abdominal cavity that normally not found. Radiological examination plays very important role to detect the presence of abnormal gas, the volume, the location, and the complication. Some of these conditions can represent classic radiological appearance that we can find in everyday practice.